Organizational readiness for implementing change in acute care hospitals: An analysis of a cross‐sectional, multicentre study. (23rd August 2018) - Sharma, Narayan; Herrnschmidt, Jenny; Claes, Veerle; Bachnick, Stefanie; De Geest, Sabina; Simon, Michael; ,
Abstract: Aim: To assess nurse‐reported organizational readiness for implementing change in acute care hospitals. Background: An organization's success at implementing new policies and programmes depends largely on its stakeholders' readiness for change. Organizational readiness is a multilevel, multifaceted construct associated with staffing, leadership and quality of care. Design: This is a secondary analysis of the cross‐sectional multicentre "Matching Registered Nurse Services with Changing Care Demands" study. Methods: In 23 acute care hospitals across Switzerland, 1, 833 nurses working in 124 units completed a survey between September 2015 and January 2016. Organizational readiness was measured with two subscales: "change commitment" and "change efficacy". Work environment factors were assessed using the Practice Environment Scale of the Nursing Work Index. Results: Nurses were positive about implementing change in their hospitals. Intraclass correlation was higher at the unit level than at the hospital level for both change commitment and change efficacy. Nursing foundation for quality of care and supportive leadership were positively associated with readiness, change commitment and change efficacy. However, staffing and resource adequacy was positively associated only with change efficacy. No association was found with standardized staffing. Conclusion: While organizational readiness scores vary among hospitals and units, they are positively associated with supportive leadership and a foundation for quality of care. Further research should consider organizational readiness as an important factor of change and ultimately of the quality of care.